Microwave-assisted 1,3-dipolar cycloaddition of azomethine ylides to [60]fullerene: thermodynamic control of bis-addition with ionic liquids additives - Martinis, Estefanía Mabel (2021)
The cycloaddition of azomethine ylides to [60]fullerene (C60) has been studied in ortho-dichlorobenzene (o-DCB) by evaluating the impact of an ionic liquid (IL) additive. The solvent effect has been addressed by evaluating the activation parameters of the cycloaddition and the boosting effect of the microwave (MW) induced dielectric heating. The IL additive plays a twofold role of stabilizing the dipolar ylide intermediate and favoring the retro-cycloaddition at high temperature regime. Under the conditions explored, a combined kinetic and thermodynamic preference favors the selective formation of trans bis-fulleropyrrolidine regioisomers, in agreement with the DFT computational analysis.